Clinical Features, Antibiotic Susceptibilities, and Outcomes of Endophthalmitis Caused by Streptococcal Infection: Children vs. Adults - Yao Yang; Yuenying Wong; Yujie Li; Fang Duan; Xinqi Ma; Hiufong Wong; Rongsha Sun; Jieting Zeng; Manli Liu; Zhaohui Yuan; Xiaofeng Lin (MDPI AG, 2023)
Streptococcus spp. are common causative organisms of endophthalmitis. Analysis of the clinical features, antibiotic susceptibilities, and outcomes of streptococcal endophthalmitis in children and adults may guide future management. Sixty-seven patients (67 eyes) with streptococcal endophthalmitis who were admitted to the Zhongshan Ophthalmic Center between January 2013 and December 2022 were retrospectively reviewed. The mean age was 20.7 ± 21.6 years, and 59.7% were children. Streptococcal infection accounted for 13.9% of culture-proven bacterial endophthalmitis cases; the proportion was higher in children than in adults (32.3% vs. 7.6%, p < 0.01) and increased from 8.1% in 2013-2017 to 20.1% in 2018-2022 (p < 0.01). Eye trauma was the most common etiology in both children and adults (82.5% and 66.7%, respectively). Viridans group streptococci were the most common isolates, followed by S. pneumoniae. The susceptibility rates of the streptococci to vancomycin, cefuroxime, and levofloxacin were 100%, 95.5%, and 93.0%, respectively. The overall mean best-corrected visual acuity increased from 2.74 ± 0.19 logMAR initially to 2.32 ± 0.75 logMAR at the last follow-up (p < 0.05). In conclusion, streptococcal infections have increased in cases of bacterial endophthalmitis in recent years and are more common in children. The commonly used antibiotics, vancomycin, cefuroxime, and fluoroquinolone, showed higher antibiotic susceptibility. After prompt treatment, visual outcomes improved.